INSURANCE FRAUD AND THE MONDAY EFFECT IN WORKERS COMPENSATION INSURANCE - Derrig, Richard A. (Assurances)

(untitled) (HEC Montréal, 2001)
Insurance fraud has come under increasing scrutiny by risk managers, company claims managers, public policymakers, and academic researchers during the last fifteen years. Workers compensation insurance has always attracted employee claimants willing to fake on-the-job injuries, particularly those hard-to-verify injuries such as soft tissue or low back pain. In addition to managing individual claims for legitimacy, risk managers must respond to injury patterns through increased safety measures, but only when those injuries are legitimate. Distinguishing between legitimate and fraudulent claims can be a daunting task. This paper considers that task for one type of claims, those filed on the first day of the week.We test the fraud hypothesis directly by using five years of available data from the Massachusetts Insurance Fraud Bureau (IFB) compared to the population of workers compensation claims for the 1990-1995 period. We find no difference in the interday distribution of substantive fraud referrals to IFB and all claims, lending additional support to the higher injury rate hypothesis for the elevated Monday claims. This result points all risk managers toward specifying additional "Monday" specific loss controls for their operations.